Temperature‐Stable Relative Permittivity from −70°C to 500°C in (Ba0.8Ca0.2)TiO3–Bi(Mg0.5Ti0.5)O3–NaNbO3 Ceramics. Issue 8 (12th May 2014) - Zeb, Aurang; Bai, Yang; Button, Tim; Milne, Steven J.; Jo, W.
<x xml:space="preserve">Abstract</x> Temperature‐stable relaxor dielectrics have been developed in the solid solution system: 0.45Ba0.8Ca0.2TiO3–(0.55 − x)Bi(Mg0.5Ti0.5)O3–xNaNbO3. Ceramics of composition x = 0 have a relative permittivity ɛr = 950 ± 15% over a wide temperature range from +70°C to 600°C. Modification with NaNbO3 at x = 0.2 decreases the lower limiting temperature to −70°C, but also decreases relative permittivity such that ɛr 600 ± 15% over the temperature range −70°C to 500°C. For composition x = 0.3, the low‐temperature dispersion in loss tangent, tan δ, (at 1 kHz) shifts to lower temperature, giving tan δ values ≤0.02 across the temperature range −60°C to 300°C in combination with ɛr 550 ± 15%. Values of dc resistivity for all samples are of the order of 1010 Ω m at 250°C and 107 Ω m at 400°C.